Exploring skin adverse events and mechanisms of apalutamide using data mining algorithms and network pharmacology - Yaqing Chen; Longzhuan Huang; Wenwei Li; Hangye Gu; Yong Chen (Frontiers in Pharmacology)
BackgroundSkin adverse events of apalutamide pose a major challenge to its clinical use, particularly the severe and difficult to identify toxic epidermal necrolysis. For the purpose of providing the basis for the clinical monitoring of the administration of apalutamide and further research. This study examined the pathways of apalutamide and Stephen Johnson Syndrome/Toxic Epidermal Necrolysis using network pharmacology and data mining tools to analyze skin adverse events.MethodsUsing the Information Component method and the Reporting Odds Ratio, the relationship between apalutamide and skin adverse events was evaluated. Molecular docking was utilized to explore the potential mechanism of apalutamide and Stephen Johnson Syndrome/toxic epidermal necrolysis.ResultsWith a median time to onset of all skin adverse events of 55 days, a total of 21 skin-related adverse events were found. Low body weight and advanced age may be major hazards for skin adverse events with apalutamide. The results showed a substantial association between apalutamide and Stephen Johnson Syndrome/toxic epidermal necrolysis, and the mechanism behind this association may be the binding of apalutamide to JAK1 and JAK2.ConclusionSpecial attention is recommended for skin adverse events when using apalutamide, especially for rapidly progressing and severe adverse events. To confirm the connection between the triad of Janus kinase, apalutamide, and skin adverse events, further research is required in the future.